PENERAPAN METODE TRUE OR FALSE DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN (PKN) TENTANG SISTEM PEMERINTAHAN REPUBLIK INDONESIA PADA PESERTA DIDIK KELAS VI SDN BEGANJING, JAPAH, BLORA - Juremi, Juremi (Jurnal Penelitian Pendidikan, 2016)
The purposes of this research are describing the application of true or false method in Civics Education learning about the System of Indonesia Republic Government in Class of VI, Beganjing Public Elementary School, Japah, Blora and analyzing the application of true or false method in Civics Education learning about the System of Indonesia Republic Government to the students’ learning result in Class of VI, Beganjing Public Elementary School, Japah, Blora. This research is a Class Action Research (CAR). The results of this research are: 1) the application of true or false method in Civics Education learning about the System of Indonesia Republic Government is using learning group, so the students are active and cooperative in learning, 2)the application of true or false method in Civics Education learning about the System of Indonesia Republic Government is analyzing the statement, so the subject mastering is getting stronger, 3) the application of true or false method in Civics Education learning about the System of Indonesia Republic Government is increasing the students’ learning result according to the increasing of average point and completeness in daily examination.